2017
DOI: 10.1016/j.hal.2017.06.009
|View full text |Cite|
|
Sign up to set email alerts
|

“Canary Islands (NE Atlantic) as a biodiversity ‘hotspot’ of Gambierdiscus: Implications for future trends of ciguatera in the area”

Abstract: In the present study the geographical distribution, abundance and composition of Gambierdiscus was described over a 600km longitudinal scale in the Canary Islands. Samples for cell counts, isolation and identification of Gambierdiscus were obtained from five islands (El Hierro, Tenerife, Gran Canaria, Fuerteventura and Lanzarote). Average densities of Gambierdiscus spp. between 0 and 2200cellsg blot dry weight of macrophyte were recorded. Morphological (light microscopy and SEM techniques) and molecular analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 49 publications
5
71
0
Order By: Relevance
“…In summary, our findings clearly show differences in the toxicities of different microalgal species and in the distribution of Gambierdiscus species between islands of the Canary Islands [22]. Moreover, the differing toxicities of different strains of the same species highlight the need to assess intraspecific and geographic variations in the distribution of CTX and MTX toxicity.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In summary, our findings clearly show differences in the toxicities of different microalgal species and in the distribution of Gambierdiscus species between islands of the Canary Islands [22]. Moreover, the differing toxicities of different strains of the same species highlight the need to assess intraspecific and geographic variations in the distribution of CTX and MTX toxicity.…”
Section: Discussionmentioning
confidence: 57%
“…Two additional episodes happened in 2008 causing the intoxication of 11 people [20]. Since then, several CFP episodes affected 113 people (Canary Government, 2017), [21,22]. Because of recurrent outbreaks, CFP has been designated as a notifiable disease in the Canary Islands since 2015 (Canary Government, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The G. excentricus strain tested in the (Litaker et al, 2017) study was~44-to 1,740-fold more toxic than the other examined species. G. excentricus is present and abundant in the eastern Atlantic (Canary Islands; Fraga et al, 2011;Rodríguez et al, 2017), and has been found in Brazil (Nascimento et al, 2015) and in the Caribbean Sea (Litaker et al, 2017). Therefore, we suggest that this species may be likely to be the causative species for the production of CTX toxins related to CFP poisoning cases in Madeira.…”
Section: Discussionmentioning
confidence: 81%
“…Recent improvements in sampling, taxonomic characterization, and sophisticated toxin detection indicate that CFP-producing species may be spreading from tropical to temperate latitudes due to global warming (Tester et al, 2010;Laza-Martínez et al, 2016;Rodríguez et al, 2017;Nishimura et al, 2018). Phenological changes may also be occurring in CFP-prevalent areas such as the Caribbean Sea (Tosteson, 2004;Nakada et al, 2018).…”
Section: The United States Caribbean Islandsmentioning
confidence: 99%